Electrochemical Sensor for Hydrogen Peroxide Based on Prussian Blue Electrochemically Deposited at the TiO2-ZrO2–Doped Carbon Nanotube Glassy Carbon-Modified Electrode - Fernández, Lenys; Alvarez-Paguay, Jocelyne; González, Gema; Uribe, Rafael; Bolaños-Mendez, Diego; Piñeiros, José Luis; Celi, Luis; Espinoza-Montero, Patricio J. (Frontiers in Chemistry, 2022)
In this investigation, a hydrogen peroxide (H2O2) electrochemical sensor was evaluated. Prussian blue (PB) was electrodeposited at a glassy carbon (GC) electrode modified with Titanium dioxide and Zirconia doped functionalized carbon nanotubes (TiO2.ZrO2-fCNTs), obtaining the PB/TiO2.ZrO2-fCNTs/GC modified electrode. The morphology and structure of the nanostructured material TiO2.ZrO2-fCNTs was characterized by scanning and transmission electron microscopy, the specific surface area was determined via Brunauer–Emmett–Teller, X-ray diffraction, thermogravimetric analysis, Raman and Fourier transform infrared spectroscopy. The electrochemical properties were studied by cyclic voltammetry and chronoamperometry. Titania-Zirconia nanoparticles (5.0 ± 2.0 nm) with amorphous structure were directly synthesized on the fCNTs walls, aged during periods of twenty days, obtaining a well dispersed distribution with a high surface area. The results indicate that the TiO2.ZrO2-fCNTs nanostructured material exhibits good electrochemical properties and could be tunable by enhancing the modification conditions and method of synthesis. Covering of the nanotubes with TiO2.ZrO2 nanoparticles is one of the main factors that affected the immobilization and the sensitivity of the electrochemical biosensor. The electrode modified with TiO2.ZrO2 nanoparticles with twenty-days aging times were superior regarding its reversibility, electric communication, high sensitivity and improves the immobilization of the PB at electrode.The fabricated sensor was applied in the detection of H2O2 in whey milk samples, presenting a linear relationship from 100 a 1000 µmol L−1 between H2O2 concentration and the peak current, with quantification limit (LQ) of the 59.78 μmol L−1 and detection limit (LD) of 17.93 μmol L−1.